Have a mice flight! - Leavitt, Lindsey (Leavitt, Lindsey. Commander in Cheese, 2016)
Ava and Dean Squeakerton, mouse siblings who live in the White House, hatch a plan to fulfill Ava's dream of flying by sneaking aboard Air Force One, the president's airplane.